A revised inventory of Annelida in the Lebanese coastal waters with ten new aliens for the Mediterranean Sea - TOSO, ANDREA; PUTIGNANO, MATTEO; FUMAROLA, LARA M.; BARICHE, MICHEL; GIANGRANDE, ADRIANA; MUSCO, LUIGI; PIRAINO, STEFANO; LANGENECK, JOACHIM (Mediterranean Marine Science, 2024)
Sampling activities conducted in the Tyre Coast Nature Reserve, southern Lebanon, to study the marine annelid fauna of the area, allowed for the revision of the diversity of this group in Lebanon. We particularly focused on non-indigenous species (NIS), which were characterised from morphological and molecular points of view. A total of 116 taxa were collected; 10 species are reported here for the first time in the Mediterranean Sea, while 6 species with presumable Indo-Pacific affinity are likely new to science. Seventy-three taxa were native, while 43 taxa were NIS; among the latter, 24 species are reported for the first time in Lebanon. Molecular data were obtained for 28 NIS, representing the first data from the Mediterranean Sea for 23 of them. Non-indigenous annelids occurring along the coast of Lebanon mainly have Indo-Pacific affinity. However, molecular data highlighted inconsistencies between the sampled material and the sequences available in public repositories, suggesting the widespread occurrence of species complexes in these taxa. These results suggest that further research on Indo-Pacific annelids is needed to understand their diversity patterns and invasion pathways. Additionally, the large number of new records of annelids in Lebanese waters indicate that further studies are needed to explore their diversity in comparison with neighbouring Mediterranean regions.